NMI: a potential biomarker for tumor prognosis and immunotherapy - He, Teng; Qiao, Yinbiao; Yang, Qi; Chen, Jie; Chen, Yongyuan; Chen, Xiaoke; Hao, Zhixing; Lin, Mingjie; Shao, Zheyu; Wu, Pin; Xu, Feng (Frontiers in Pharmacology, 2022)
N-Myc and STAT Interactor protein (NMI) is an interferon inducible protein involved in various cellular activities, which is widely involved in the process of tumorigenesis and progression. Studies have shown that the loss of NMI expression in breast cancer can promote its progression by inducing epithelial-mesenchymal-transition (EMT). However, the expression level of NMI in other tumors and its impact on immune cell infiltration, patient prognosis, and drug treatment are still unclear. Here, we analyzed the role of NMI in pan-cancer through multiple omics data. We found that NMI was abnormally expressed in a variety of tumor tissues. The expression of NMI is closely related to the unique molecular and immunotyping, diagnosis and prognosis of various tumor tissues. In addition, we identified the main proteins that interact with NMI, and focused on the relationship between the clinical parameters of lower grade glioma (LGG) and NMI expression. Subsequently, we found that the expression of NMI was correlated with the infiltration of multiple immune cells and the expression of immune checkpoints. Finally, we also found that the expression of NMI was correlated with the sensitivity of multiple antitumor drugs. In conclusion, our comprehensive pan cancer analysis of NMI revealed that it is a potential molecular marker for tumor diagnosis and treatment and plays an important role in tumor immunity, and is a promising molecular target for cancer treatment.